2013
DOI: 10.1080/13825585.2012.679914
|View full text |Cite
|
Sign up to set email alerts
|

Episodic intertrial learning of younger and older adults: Effects of word frequency

Abstract: Older adults have a demonstrable episodic memory deficit. The present study aimed to investigate whether the age deficit in episodic memory was influenced by stimulus characteristics known to produce differences in memory performance in younger adults, specifically word frequency. An intertrial paradigm was used whereby participants studied high- or low-frequency lists over several study-test trials, and the loss and gain of individual items was measured across trials; putative measures of consolidation and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 57 publications
4
25
3
Order By: Relevance
“…In addition, although there is no significant difference in word frequency and age of acquisition between the two tests, Almond et al (2013) [20] found that high-frequency words are learned at a higher rate than low-frequency words in older adults compared to younger adults, which indicates that the memory deficits may be modulated by word frequency. However, the number of words used in the present study is too limited to be separated into high and low frequency words for further statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, although there is no significant difference in word frequency and age of acquisition between the two tests, Almond et al (2013) [20] found that high-frequency words are learned at a higher rate than low-frequency words in older adults compared to younger adults, which indicates that the memory deficits may be modulated by word frequency. However, the number of words used in the present study is too limited to be separated into high and low frequency words for further statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This can be deduced from the slope of the learning curve in multiple learning trials. Learning rate has been found to be sensitive to age-related memory deficits and even to stimuli characteristics (word frequency) in older adults [20]. People with cerebral lesions in different brain locations also showed different learning rates [21].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations